PELATIHAN PENGEMBANGAN MEDIA BERBASIS GAME UNTUK GURU MATEMATIKA DI SMP NEGERI 8 DENPASAR - I Gusti Agung Ngurah Trisna Jayantika; I Wayan Sumandya; Ni Kadek Rini Purwati; Ni Luh Made Manik Widayani (LPPM Universitas PGRI Mahadewa Indonesia, 2022)
The service, which was carried out at SMP Negeri 8 Denpasar, involved teachers at SMP Negeri 8 Denpasar. This activity aims to provide training to teachers to develop games-based media-assisted learning designs. This activity is divided into four activities, namely socialization, training, mentoring and evaluation. The implementation of this activity begins with socialization with school principals regarding the service program to be carried out, providing training on developing learning designs with games-based media, providing assistance in implementing learning with games-based media, donating game-based media packages, namely Domas media, and carry out an evaluation of the service program carried out. The results of this service conclude that there is an increase in the ability of teachers related to game-based media, 2) teachers can design learning by integrating game-based media, 3) teachers have innovation and variety in learning activities in class.